A novel homozygous RSPH4A variant in a family with primary ciliary dyskinesia and literature review - Shen, Chenling; Shen, Yilin; Huang, Weiyi; Zhang, Andi; Zou, Tianyuan; Guo, Dongye; Wang, Hao; Wu, Jichang; Hu, Haixia; Xiang, Mingliang; Ye, Bin (Frontiers in Genetics, 2024)
Primary ciliary dyskinesia (PCD) is a rare heterogeneous disease caused by abnormalities in motile cilia. In this case report, we first analyzed the clinical and genetic data of a proband who was suspected of having PCD on the basis of her clinical and radiological findings. Whole-exome sequencing was performed, and a variant in the RSPH4A gene was identified in the proband. Sanger sequencing was used for validation of RSPH4A variants in the proband, her sister, her daughter and her parents. Finally, the phenotypic features of the patient were analyzed, and the current literature was reviewed to better understand the gene variants in PCD related to hearing loss and the clinical manifestations of the RSPH4A variant in PCD. The chief clinical symptoms of this proband included gradual mixed hearing loss, otitis media, anosmia, sinusitis, recurrent cough and infertility. Her DNA sequencing revealed a novel homozygous T to C transition at position 1321 within exon 3 of RSPH4A according to genetic testing results. This variant had never been reported before. The homozygous variant resulted in an amino acid substitution of tryptophan by arginine at position 441 (p.Trp441Arg). The same variant was also found in the proband's sister, and a heterozygous pathogenic variant was identified among immediate family members, including the proband's daughter and parents. A literature review showed that 16 pathogenic variants in RSPH4A have been reported. Hearing loss had only been observed in patients with the RSPH4A (c.921+3_6delAAGT) splice site mutation, and the specific type of hearing loss was not described.